Engineers as Key Players for Sustainability: The Role of Pse Academia - Azzaro-Pantel, Catherine; Dal Pont, Jean-Pierre (New Appoaches in the Process Industries, 2014)
This chapter explores why process systems engineering (PSE) is particularly well suited among chemical engineering curricula to reach the sustainability challenges. In process industries, many leading corporations have adopted the concept of sustainable development and environmental protection and social responsibility have been identified as important to both shareholders and other stakeholders. Sustainability in engineering can be viewed as a shift in engineering that reflects changes in the issues affecting our transitioning world. The range of options for teaching the subject can be wide, with no prescribed approach. The objective of the chapter is just to give some ideas in order to overcome the above mentioned barriers, since one major role of academia is to spur innovation. Several tiers of engagement to place sustainability at the core of engineering curricula can be considered according to the pedagogical target.